CROSS-NATIONAL GENDER DIFFERENCE COMPARISONS IN THE RECEIPT OF HOME CARE AMONG OLDER ADULTS IN US, KOREA, AND CHINA - Kwak, M (Innov Aging, 2018)
This study examines gender differences in the receipt of informal and formal care among older adults in communities across the US, Korea, and China where family-oriented systems for elder care are emphasized. We used data from the 2014 Health and Retirement Study, 2014 Korea Longitudinal Study of Aging, and 2015 China Health and Retirement Longitudinal Study. We also used logistic regression models and tested interactions between gender and living arrangement as well as health. Results indicated that, in the US and China, older women are more likely than men to receive informal care. However, older Korean women are less likely than men to receive informal care. Older American and Korean women are more likely than men to receive formal care. No gender differences were observed in China. The effects of living arrangement and functional disabilities on the receipt of informal and formal care were moderated by gender. This study provides evidence that patterns of gender differences in the receipt of care vary across the three countries. In particular, older Korean women may be more likely than men to be exposed to risk of unmet needs. In the US, older men living alone are vulnerable to unmet needs. In China, women with severe disabilities are disadvantaged in receipt of informal and formal care compared to their male counterparts. More attention should be paid to designing and implementing social policies and programs for elder care to address different patterns of gender disparities in the receipt of care in each country.